Associations of specific dietary unsaturated fatty acids with risk of overweight/obesity: population-based cohort study - Chen, Weiming; Ao, Yang; Lan, Xiaochun; Tong, Wenzhou; Liu, Xiaohui; Zhang, Xia; Ye, Qiang; Li, Yin; Liu, Linfen; Ye, Hao; Zhuang, Pan; Zhang, Yu; et al. (Frontiers in Nutrition, 2023)
Background: The role of specific unsaturated fatty acids (FAs) in the development of overweight/obesity remains unclear in the general population. Here, we aimed to explore the associations of different types of unsaturated FAs with overweight/obesity risk among the Chinese population. Methods: 8,742 subjects free of overweight/obesity at entry in the China Health and Nutrition Survey (CHNS) were followed up until 2015. Dietary unsaturated FAs were assessed by 3-day 24-h recalls with a weighing method in each wave. Cox regression models were used to obtain the hazard ratios (HRs) and 95% confidence intervals (CIs) for overweight/obesity risk associated with unsaturated FAs. Results: During a median follow-up of 7 years, 2,753 subjects (1,350 males and 1,403 females) developed overweight/obesity. Consuming more monounsaturated FAs (MUFAs) was associated with a lower risk of overweight/obesity (highest vs lowest quartile: HR 0.80, 95% CI 0.67-0.96; P-trend = 0.010). Similar inverse associations were observed for plant-MUFA (HRQ4vsQ1 0.83, 95% CI: 0.73-0.94; P-trend = 0.003) and animal-MUFA (HRQ4vsQ1 0.77, 95% CI: 0.64-0.94; P-trend = 0.004), total dietary oleic acid (OA) (HRQ4vsQ1 0.66, 95% CI 0.55-0.79; P-trend < 0.001), plant-OA (HRQ4vsQ1 0.73, 95% CI: 0.64-0.83; P-trend < 0.001) and animal-OA (HRQ4vsQ1 0.68, 95% CI: 0.55-0.84; P-trend < 0.001). In addition, intakes of n-3 polyunsaturated FAs (PUFAs) (HRQ4vsQ1 1.24, 95% CI 1.09-1.42; P-trend = 0.017) and α-linolenic acid (ALA) (HRQ4vsQ1 1.22, 95% CI 1.07-1.39; P-trend = 0.039) but not marine n-3 PUFAs were positively linked to overweight/obesity risk. Consumption of n-6 PUFA (HRQ4vsQ1 1.13, 95% CI 0.99-1.28; P-trend = 0.014) and linoleic acid (LA) (HRQ4vsQ1 1.11, 95% CI 0.98-1.26; P-trend = 0.020) had marginal and positive relationships with the incidence of overweight/obesity. N-6/n-3 ratio ranging from 5.7 to 12.6 was related to higher risk of overweight/obesity. Conclusions: Higher dietary intake of MUFAs was associated with lower overweight/obesity risk, which was mainly driven by dietary OA from either plant or animal sources. Intakes of ALA, n-6 PUFAs and LA were related to higher risk of overweight/obesity. These results support consuming more MUFAs for maintaining a healthy body weight among the Chinese population.